Halibee member archaeology: Middle Stone Age environment, technology, and postmortem modifications - Yonas Beyene; Berhane Asfaw; Tim D. White; Giday WoldeGabriel; Raymond Bernor; Faysal Bibi; Jean-Renaud Boisserie; Marianne F. Brasil; Christopher A. Brochu; Joshua P. Carlson; Nuria G. García; Ioannis X. Giaourtsakis; et al. (Proceedings of the National Academy of Sciences, 2026)
The Middle Awash study area of Ethiopia’s Afar Rift features a composite stratigraphic thickness of >1 km. Near the top of this succession lie sediments of the lower Halibee member, comprising the Faro Daba and Chai Baro beds. The former are radioisotopically dated to ~100,000 y in age and contain abundant fossils and associated lithic artifacts representing the Middle Stone Age (MSA). Geological, paleontological, and archaeological datasets recovered from these sediments enlarge a sparse later Pleistocene record of African human evolution, a time before anatomically modern populations of our species expanded into Eurasia. The Faro Daba occurrences comprise the richest, least disturbed, and most spatially extensive of many open-air MSA-bearing localities in the study area and beyond. Protected atop a resistant underlying conglomerate, the largely horizontal outcrops of the soft, eroding fossiliferous Faro Daba sediments provide spatially extensive access to in situ assemblages of artifacts and fossils. Sedimentology, faunal composition, and combustion features are consistent with a wooded depositional environment with seasonal flooding distant from the main river channel. Archaeological and paleontological assemblages indicate minimal postdepositional disturbance of primary lithic tool manufacture and discard during ephemeral human occupations on this floodplain. Among the recovered fossils are three partial human skeletons with taphonomic evidence of different postmortem pathways.